In-vitro corrosion properties of quaternary Mg-Zn-Re-xCa alloys for biomedical applications - Joy Yii Sze Li, 1988- author; Esah Hamzah; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2014